2022
DOI: 10.1111/1751-7915.14189
|View full text |Cite
|
Sign up to set email alerts
|

Development of a live biotherapeutic throat spray with lactobacilli targeting respiratory viral infections

Abstract: Respiratory viruses such as influenza viruses, respiratory syncytial virus (RSV), and coronaviruses initiate infection at the mucosal surfaces of the upper respiratory tract (URT), where the resident respiratory microbiome has an important gatekeeper function. In contrast to gut-targeting administration of beneficial bacteria against respiratory viral disease, topical URT administration of probiotics is currently underexplored, especially for the prevention and/or treatment of viral infections. Here, we report… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 67 publications
(90 reference statements)
0
7
0
Order By: Relevance
“…The more established strains, notably those that belong to the Lactobacillaceae family, are already widely utilised and have a known safety profile. It has been proposed that lactic acid bacteria (LAB) can rebuild commensal microbiomes [ 16 , 27 , 65 ]. It is worth noting that LAB are part of the microbiome of the upper respiratory tract [ 31 , 60 , 62 ].…”
Section: Microbiome In Chronic Rhinosinusitismentioning
confidence: 99%
See 1 more Smart Citation
“…The more established strains, notably those that belong to the Lactobacillaceae family, are already widely utilised and have a known safety profile. It has been proposed that lactic acid bacteria (LAB) can rebuild commensal microbiomes [ 16 , 27 , 65 ]. It is worth noting that LAB are part of the microbiome of the upper respiratory tract [ 31 , 60 , 62 ].…”
Section: Microbiome In Chronic Rhinosinusitismentioning
confidence: 99%
“…L. casei AMBR2 is a promising candidate for a live biotherapeutic product as a probiotic. It has the ability to inhibit the growth and inflammatory properties of pathogens such as Staphylococcus aureus and to promote epithelial barrier function [ 34 , 65 ]. Thus, there is a lot of interest in further using this strain in CRS patients.…”
Section: Therapeutic Applications Of Lactic Acid Bacteria Probioticsmentioning
confidence: 99%
“…Probiotics have proven to be a good strategy for the modulation of the human intestinal and vaginal microbiota, as well as to stimulate the systemic and mucosal immune response to prevent and treat infectious diseases (De Boeck et al, 2021 ; Håkansson et al, 2019 ; Spacova et al, 2023 ). Several authors reported the SLP's role in antimicrobial properties and immune activation.…”
Section: Slps Applicationsmentioning
confidence: 99%
“…Similarly, polymeric nanoparticles, solid lipid nanoparticles, and dendrimers are also being explored as inhalable drug carriers (Barthold et al., 2023). However, research in the field of probiotics, postbiotics, and their potential use in inhalers treatments, continues to expand (Spacova et al., 2023). The majority have been developed as suspension for nasal administration against SARS‐CoV, influenza ssp, streptococcus and pneumococcal infection (Table 2).…”
Section: Introductionmentioning
confidence: 99%